Histological and some histocltemical obsen’ations on stomach and gastrıc glands of rabbits (Oryctolagus cuniculus huxleyi ) (Annals of Medical Research, 2021)
None
Keywords: s : Rabbit, stomach, lıistologv, histoehemie.